Polyform reinforcing the dynamic nature of math in the real world through immersive mobile games - Domingo, Maeves R.; San Valentin, Marc (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
The connection is missing. This is what I have inferred after my data gathering and interviews with students and simply the common aversion towards Math. Students have asked and requested to learn more on how they can apply the Math they are leaning in real life. This alone already presents the problem on how students are failing to see the presence and application of Math in our daily lives. Without seeing its importance in real life, there bears fruit the aversion towards Mathematics.Teachers may have already developed their lesson plans, referring more often where the Math lesson is present in our daily activities. Visual teaching and learning styles have already been adapted by institutions to make the subject feel more approachable, fun and non-numerical based. But there is so much more one can do than just reforming the classroom lecture to be different and fun by adapting visual aids or techniques. After all, Math is a way of thinking in and outside school grounds. My thesis aims to elucidate how upper elementary students can continually value and apply math in their daily activities. To further highlight the dynamic nature of Math, I have taken it outside the classroom setting. I have looked into the idea of a collaborative mobile game that revolves around the application of math in various real world activities. My game plan was driven by the idea of physical objects interacting with digital games as an ability to influence the process and outcome. With this, players are also given a chance to play around and explore in their own mind space while still gearing towards a learning objective. Moreover, integration of real world scenarios underlines the presence and relevance of Math within them, thus reinforcing the true dynamic nature of Mathematics in the real world.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 102-103.
Keywords: Games in mathematics education; Mobile games